The Great Emperor Asoka’s Rock Edict In Delhi (Bodhi Path, 2023)
It’s a great pride for India, the Great Emperor Aśoka was born here who had propagated and expanded Buddhism almost throughout Asian Subcontinent and the people of the human world remember him with great respect. He was credited and honoured for raising Buddhism to the principal religion of the world. The famous writer of Britain H.G.Wells is considered “The Great Emperor (Cakerverty Samarat) Aśoka (c 273BCE -232 BCE)” as one of the six greatest personalities -Tathāgata Buddha, Socrates, Aristotle, Rogar Bacon, and Abraham Lincon and The Cakerverty Samarat Aśokai of the world in the history since the time immemorial. The human world including India did not know anything about him before 1837 C.E. when the English scholar and Assay Master, James Prinsep (1799 CE-1840CE) was enabled to decipher the script of inscriptions with the help of bilingual coins of the Indo-Greek rulers of North–West Jambudvipa and outcrop the truth over the myths spread through out of India about these inscriptions. Cakerverty Samarat Aśoka was the legendary personality of Jambudvipa who ruled over the country for about thirty eight years with rule of Dhamma; the righteousness. He was well established Buddhism which he propagated as Dhamma in the history of Asian Subcontinent. He was a spontaneous, ardent and patron of Buddhism who had left behind thousands of inscriptions; those are spreading teachings of Dhamma in his entire empire; Jambudvipa for the benevolence of all sentient beings and also among the neighbouring countries. Eighty four thousand monuments in the form of edifices, monasteries, inscriptions, stups, catyas, caves etc. were formed during his kingdom through the length and breadth of Jambudvipa.
Keywords: Asoka’s Rock Edict In Delhi